Evaluation Of The Decision Of The Palembang District Court Number 156/Pid.B/2024/PN.Plg From A Criminal Law Perspective In The Police Recruitment Process - Mahendra, Yusuf Eka; Fahrian, Yudi; Agustina, Sakinah (Fakultas Hukum Dehasen, 2025)
This research is entitled Evaluation of Palembang District Court Decision Number 156/Pid.B/2024/Pn.Plg From a Criminal Law Perspective in the Police Recruitment Process. This case is interesting to examine because it reflects legal irregularities in the recruitment process for prospective Polri members which should be carried out in a clean, transparent, accountable, and humane manner. The defendant, who is not part of the police institution, promised the victim that he could pass his child to become a Polri member in exchange for a sum of money that was ultimately not returned. The problem of this research is what form of criminal liability is applied and how the judge's considerations in the decision. This research uses a normative juridical method with a case study approach through a literature study that includes primary legal materials in the form of the Criminal Code, Police Chief Regulations, and court decisions, as well as secondary legal materials from literature and opinions of legal experts. The analysis is carried out qualitatively by describing legal facts, criminal elements, and relevant theories of criminal liability such as strict liability, responsibility, and accountability. The research results indicate that criminal liability is based on the principle of culpability, applying the theories of responsibility and accountability, as the defendant possesses the legal capacity to take responsibility and is proven to have committed the offense intentionally. The defendant was found guilty of Articles 372 and 378 of the Criminal Code concerning embezzlement and fraud, and the panel of judges sentenced him to two years and six months in prison. However, the judge should have considered Article 65 of the Criminal Code, which regulates the combination of crimes with similar penalties, thus requiring a sentence of four years and three months, along with an obligation to pay compensation to the victim. Furthermore, non-penal measures are also important, including public education using social media to ensure public awareness that recruitment into the Indonesian National Police (Polri) is free, and to encourage the police institution to be more transparent and decisive in prosecuting individuals involved, including dismissal and criminal proceedings. Therefore, this research is expected to contribute to strengthening legal justice, increasing recruitment transparency, and raising public legal awareness.